White Collar Crime and Risk Financial Crime, Corruption and the Financial Crisis (Palgrave Studies in Risk, Crime and Society, 2018)
This edited collection provides an innovative and detailed analysis of the relationship between the financial crisis, risk and corruption. A large majority of the published research has concentrated on identifying the traditional factors that contributed towards the largest financial crisis since the Wall Street Crash and subsequent Great Depression. This original volume contests this, and provides the alternative view that white collar crime was also an underappreciated, and important factor. Divided into five parts: bribery and corruption; financial crime; market manipulation; technology and white collar crime; and the financial crisis, and based on contributions by a wide range of experts in the field, this book will be of great interest to policy makers and practitioners, researchers and students alike.